2022
DOI: 10.3126/nmcj.v24i1.44145
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Extended Spectrum Beta Lactamase producing Escherichia coli and Klebsiella spp. from urinary specimen in a tertiary care hospital

Abstract: Escherichia coli and Klebsiella spp. are two important uropathogens showing resistance to beta-lactams by producing extended spectrum beta lactamase (ESBL), leading to difficulty in treating infections with these bacteria. Majority of the ESBLs are of TEM, CTXM and SHV types reported from Nepal. This study was conducted in Clinical Microbiology Department of Nepal Medical College Teaching Hospital from November 2021 to mid-January 2022 to determine prevalence of ESBL and antimicrobial susceptibility pattern am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…It was found that the highest number of E. coli isolates was recovered from urine .With regard to urinary tract infection, E. coli showed great extent of resistance to nalidixic acid, co-trimoxazole and third generation cephalosporins. A similar pattern of resistance in urinary isolates of E. coli was shown in Nepal [ 9 , 10 ]. In contrast to our results, Fanta et al reported 73% E. coli isolates were ceftriaxone-resistant [ 11 ].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…It was found that the highest number of E. coli isolates was recovered from urine .With regard to urinary tract infection, E. coli showed great extent of resistance to nalidixic acid, co-trimoxazole and third generation cephalosporins. A similar pattern of resistance in urinary isolates of E. coli was shown in Nepal [ 9 , 10 ]. In contrast to our results, Fanta et al reported 73% E. coli isolates were ceftriaxone-resistant [ 11 ].…”
Section: Discussionsupporting
confidence: 72%
“…The prevalence of ESBL E. coli was 66.56% (215/323), which was alarmingly high. Several studies reported high prevalence i.e.40–70% of ESBL E. coli among MDR E. coli [ 10 , 15 , 17 , 22 , 23 ]. However, the study by Onyedibe et al in 2018 observed only 18.6% ESBL E. coli [ 24 ], which is an analogous result to other study [ 25 ].…”
Section: Discussionmentioning
confidence: 99%